Living weritage village of Kampung Morten Melaka: local community involvement in tourism - Ab. Rahman, Syakir Amir; Mohd Fauzi, Wan Amerul Akhyar; Bachok, Syahriah; Asmawi, M. Zainora; Ponrahano, Zakiah; Rosni, Nur Aulia; Masuda, Yukihiro; Najib, Nadiah (Secholian Publication, 2021)
Community-based Tourism (CBT) involves high community participation at the highest level of decision-making processes, to economic involvement and the giving opinion of the lowest level goal. The purpose of this study is to explore the local community participation in the tourism activities in Kampung Morten, Melaka. The questionnaire survey was conducted using a simple random sampling method among 152 respondents and the results were analysed using crosstabulation analysis. The main findings are the majority of respondents participated in tourism activities and deliberation in tourism activities. Less number of respondents were giving opinions on tourism development and plans. This study is benefitable to the tourism stakeholders to ensure the relevancy of communities staying in living heritage villages to contribute to the domestic tourism industry.